1996
DOI: 10.1111/j.1348-0421.1996.tb01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of OspA Serotypes for Borrelia burgdorferi Sensu Lato from Japan, Europe and North America

Abstract: 1.B. burgdorferi sensu stricto has not been observed in Japan, 2. Japanese B. afzelii isolates are closely related to those from Europe, 3. B. garinii isolates from Japan are highly heterogeneous and apparently different from European B. garinii isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…garinii has been previously reported (6,20,(28)(29)(30). This heterogeneity might explain the wide vector tolerance of B. garinii for the two closely related tick species and I. persulcatus (6), and adaptation to birds and small rodents (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…garinii has been previously reported (6,20,(28)(29)(30). This heterogeneity might explain the wide vector tolerance of B. garinii for the two closely related tick species and I. persulcatus (6), and adaptation to birds and small rodents (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Given the higher sensitivity and the possibility of storing the slides for several months, the direct or IFA can be considered as the method of choice to determine Borrelia infection in ticks. In principle, it allows the specific detection of Borrelia genospecies and detection of outer-surface protein expression when appropriate monoclonal antibodies are applied (Wilske et al, 1993Fingerle et al, 1995 ;Masuzawa et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, the high degree of variability of OspA has been well documented. The OspA of strains belonging to B. burgdorferi sensu stricto, B. afzelii and B. japonica are homologous within species, but not among those of strains belonging to B. garinii isolated in Europe (22,30,32,33). On the other hand, it has been demonstrated that vaccination with recombinant OspC protected gerbils from experimental challenge with a Borrelia (26).…”
mentioning
confidence: 99%
“…We previously showed that Japanese isolates (OspA serotype J1 to J9) identified as B. garinii were antigenically different from European B. garinii isolates (OspA serotypes 3 to 7) by the OspA serotyping system (22,33). No cross-protection was obtained with a heterologous vaccine prepared using isolates from Europe and…”
mentioning
confidence: 99%
See 1 more Smart Citation